Beyond the success/failure of travelling urban models: Exploring the politics of time and performance in Cape Town's East City. (September 2021) - Robin, Enora; Nkula-Wenz, Laura
In this paper, we highlight the importance for policy mobility research to engage with the 'multiple temporalities' of globally prevalent urban policy ideas to understand how these eventually come to shape localities incrementally, and as we show, in sometimes unexpected manners. Through the study of over 10 years of (failed) redevelopment policies in Cape Town's East City, we formulate two distinct contributions to existing urban policy mobility research. Firstly, we show that looking at the micro-politics of policy mobility in particular places, and over time, can help elucidate how conflicts and resistance to globally mobile urban models shape which aspects of a policy solutions are rendered mobile or immobile, present or absent and, finally, what ends up being implemented in the local context through specific projects. Secondly, we expand on new materialist approaches to urban policy mobility, bringing insights from performativity theory, to look at how ideas and models come to be 'enacted' in the real world through various and, perhaps more importantly, uncoordinated means. Our case study shows that policy mobility research should attend to disparate, uncoordinated, more-than-human activities, and how these end up shaping places even in the absence of purposive planning. That way, we show how changing and complex configurations of more than human networks, objects, money, buildings, etc. support the concrete performance of abstract and mobile urban models – in place and over time.